On the fundamental solution of the Cauchy problem for equations with negative genus and dissipative parabolicity - Litovchenko, Vladyslav (My University, 2022)
One class of differential equations with partial derivatives and variable coefficients, which have dissipative parabolicity and negative genus, is considered. For this class, the Green's function of the Cauchy problem was constructed by the method of successive approximation and its main properties were investigated